CHILL: a system for fine-grained mapping of chained high impact long-latency load phases on tightly coupled heterogeneous multi-cores. (2017) - Chen, Robert; Reinman, Glenn
With increasing power and application demands, heterogeneous multi-core processors are becoming more prevalent. However, the key to proper utilisation of heterogeneous multi-cores is assigning, or mapping, the right application to the right core type. Recent work has shown that fine-grained mapping takes advantage of short program phases with highly variant performance requirements, and can elicit greater benefits from tightly coupled heterogeneous multi-cores. In this paper, we show that bottlenecks in performance can occur in fine-grained program phases during chains of high impact long-latency loads. We design a system that detects these bottleneck phases, and propose accelerating these phases on the out-of-order core for better performance and energy efficiency. Our system operates within 10% of performance, and 2.6% of energy to an oracle resource mapper. This translates to a 44.4% performance gain, and 9.2% energy savings over existing fine-grained mapping techniques.